Implementasi Dana Corporate Social Responsibility (CSR) terhadap Kesejahteraan Masyarakat dan Kelestarian Lingkungan: (Studi Kasus PT. Bumi Daya Agrotamas Kota Subulussalam) - Syukri Syukri; Rabiatul Adawiyah; Muhaddis Muhaddis (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
PT. Bumi Daya Agrotamas aims to put pressure on the world of work to be better in carrying out all its production activities so that companies not only think about achieving maximum financial profits but also participate in preserving the environment around which the company is established... these impacts can be in the form of beneficial impacts and detrimental impacts. For companies, the various impacts are that companies oriented towards the economic aspect (profit) are also required to have a responsibility, both to the social aspect and to the environmental aspect. Based on the research background above, the author is interested in conducting research with the title "implementation of PT corporate social responsibility (CSR) funds. Bumi Daya Agrotamas towards community welfare and environmental sustainability. This research was conducted to analyze the implementation of PT's corporate social responsibility (CSR) funds. Bumi Daya Agrotamas towards community welfare and environmental sustainability. This research uses qualitative with descriptive research type, data collection techniques are observation, interviews and documentation. The data obtained was analyzed using a qualitative analysis model. The results of the research show that the implementation of corporate social responsibility (CSR) funds impacts community welfare and environmental sustainability in PT case study. Bumi Daya Agrotamaskota Subulussalam. There are still many things lacking in being able to provide maximum results for the community and good cooperation between the company and the assisted community so there is still something that needs to be improved by the PT. Bumi Daya Agrotamas so that in the future there will be no social jealousy towards the PT and also here, openness is needed by the PT. Bumi Daya Agrotamas to the community so that the closeness becomes more positive and nothing undesirable happens in the future. Furthermore, corporate social responsibility (CSR) is a form of company activity in managing business to produce positive actions in the community to create a quality community.